Co-combustion performance of oil palm trunk biocoal blended with subbituminous coal - Mohd Nudri, Mohd Nadly Aizat (2020)
1.36 compared with the raw OPT. However, the energy yield was low (37.6%) due to the low biocoal yield of 27.8%. In addition, the ash content is increased by the factor of 1.5. The increment may amplify the effects of slagging and fouling in the furnaces and boilers as shown by the slagging and bed agglomeration indices which increased from 2.0 to 5.2 and from 0.4 to 0.7, respectively. For the combustion testing, the emissions of SO2 and NOx of all samples were below the emission limits. Blend composition with 20% biocoal and 80% coal has the best criteria tested, which has high combustion efficiency and also relevantly low CO2, NOX and SO2 emissions, compared to the 100% coal. ANOVA analysis implied that temperature has major influence over the CO2 emission than air flowrate, while the latter has higher influence on the combustion efficiency. The regression model indicates excellent fit of the data to the model. Maximum combustion efficiency of 92.16% and CO2 concentration at 16.38% were predicted to be obtained under optimized operating factors of 774.33 °C and 7.84 litre per minute with desirability of 0.896. These predictions were validated with the obtained experimental values of CO2 concentration of 16.59% and combustion efficiency of 91.63%, which are within 5% deviation from the predicted values. These findings shown that better combustion performance can be attained with the co-combustion of OPT biocoal and sub-bituminous coal, rather than sub-bituminous alone in the current practice of coal-fired power plants. XRD analysis has shown that the ash formed are almost equally crystalline and amorphous, proving that both sub-bituminous coal and biocoal are present in the sample. The detected mineral phases shown that silicone dominated the chemical compounds formed in the ash. The formation of some of the minerals also indicates the interaction between elements present in both sub-bituminous coal and OPT biocoal. Based on these findings, OPT biocoal has promising potential to supplement sub-bituminous coal as solid fuel to generate energy due to its lower CO2 concentration and higher combustion efficiency relative to sub-bituminous coal, as well as comparable physicochemical characteristics. However the other properties such as mass and energy yields, handling capacity as well as the ash behaviour are need to be improved in future studies